Pork: why we should not give it up completely - Małgorzata Szamocka; Monika Anna Ameryk; Maciej Świątkowski (Kazimierz Wielki University, 2017)
It is commonly thought that cases of life shorter than the life expectancy for Poles, mainly due to atherosclerosis and certain malignancies, are caused by, among other factors, consumption of large quantities of meat, especially pork. However, essential statistical data do not confirm this hypothesis, as an average Pole eats 41,1 kg pork per year, compared to 66.1 kg eaten by Spaniards, 64.2 kg by Danes, 59.9 kg by Austrians, 53.3 kg by Germans, while the average life expectancy for female and male Poles is 80.1 years and 71.5 years, respectively, and that for female and male Western Europeans is 82,2 years and 75 years, respectively. Meat is a necessary component of human diet because of its unique chemical composition, nutritional value and content of complete protein with favorable proportions of amino acids. Pork, whose nutritional value and pro-health properties have improved over the last 20 years, has a lower content of saturated fatty acids (SAFA) and a higher content of polyunsaturated fatty acids (PUFA) compared to beef. Compared to poultry meat, pork has a significantly better proportion of essential unsaturated fatty acids (EUFA), omega-3 (PUFA n-3) to omega-6 (PUFA n-6), whose excess is typical for the so-called "Western" diet. Cholesterol content is fairly similar in all parts of pork carcass, and it is much smaller than even 20 years ago. In comparison with other meat types, pork is characterized by 4-5 times higher content of vitamin B1. Pork is also characterized by a high content of readily available iron, a very often inadequately supplied mineral in humans. It is present in the quantity of 0.014 g/kg, which is higher than in poultry meat (0.009 g/kg) but lower than in beef (0.026 g/kg). In 2015, the International Agency for Research on Cancer (IARC) updated its classification of carcinogenic agents. Red meat and processed meat were classified by IARC to group 2.A: substances probably carcinogenic to humans.  In its document, the international IARC workgroup revealed that consumption of meat brings health benefits, but consumption of processed and red meat should be limited as it can be associated with an increased risk of death due to atherosclerosic diseases and certain malignancies. Concurrently, it is noted that the results of many studies in this area are not clear. Production of genetically modified food is a very interesting, but also controversial area of studies of food, including pork.